Economic Boom and Busts Lead to Human Capital Changes? Evidence From Health Expenditure Changes in Emerging Economies - Zhang, Yichi; Deng, Wei; Afzal, Ayesha; Tao, Ran (Frontiers in Public Health, 2022)
This paper assesses data from 16 emerging economies between 2000-and 2020 to assess the relationship between business cycles and healthcare expenditure alongside other control variables. Using the Gaussian mixture model, this study analyses the relationship between healthcare spending and business cycles, urbanization, population age, environmental quality, and the gender ratio. The paper finds that there exists a counter-cyclical relationship between economic booms/recessions and healthcare expenditure such that spending decreases during booms and goes up during recessions. The study also finds evidence that environmental quality plays a vital role in influencing healthcare expenditure.